Chief executive officer compensation and the effect on company performance in a South African context - Bradley, Samuel (Rhodes University, Faculty of Commerce, Department of Accounting, 2012)
The goal of this research was to determine, in a South African context, whether there is any correlation between chief executive officer compensation and the performance of the company. For the purposes of the research , the compensation of chief executive officers was broken down into three components: salary, bonus and "other" remuneration, while company performance was measured on return on equity, return on assets and earnings per share figures. Studies on this topic have been carried out in other countries, most notably in the United States of America and the United Kingdom. It appears that no research of a similar nature has been carried out in South Africa. Data in respect of the forty largest listed companies in South Africa were collected over a period of five years. The econometric models used for the research were based on models identified in the literature study. The data were then analysed for evidence of a correlation between chief executive officer compensation and the performance of the company. The results of this study indicate that there is no linear relationship between chief executive officer compensation and company performance variables. The econometric models did, however, show correlations between certain variables, taking into account the other predictor variables in the model. Evidence of correlations between age and experience and compensation was also found , which may present potential avenues of research to scholars in the future.
Keywords: Chief executive officers -- Salaries, etc. -- South Africa; Compensation management -- South Africa; Wage surveys -- South Africa; Organizational effectiveness -- Evaluation